Inferring Jovian Electron Densities Using Plasma Wave Spectra Obtained by the Juno/Waves Instrument. Issue 8 (13th August 2021) - Sulaiman, A. H.; Elliott, S. S.; Kurth, W. S.; Faden, J. B.; Hospodarsky, G. B.; Menietti, J. D.
Abstract: The Waves instrument onboard the Juno spacecraft has plasma wave‐measuring capabilities using a single electric dipole antenna and a uniaxial magnetic search coil. Together, these simultaneously measure electric and magnetic field spectral densities in the frequency range 50 Hz–20 kHz, above which only electric field spectral densities are measured up to 41 MHz. A major objective of the Juno mission is to explore Jupiter's high‐latitude magnetosphere and ionosphere. One of the key contributions of the Waves instrument is the determination of electron densities from plasma wave spectra. Given the very high magnetic field strengths near Juno's perijove passes, established techniques cannot be utilized to infer electron densities since such highly magnetized space plasma conditions have not previously been met in planetary missions. By revisiting theoretical treatments of plasma waves, we describe a novel method to determine electron densities from plasma wave spectra that is unique to the near‐Jupiter region. In the absence of the commonly observed upper hybrid resonance frequency in high‐density space plasmas (e.g., the vicinities of Io, Ganymede, Enceladus, and the near‐Earth environment), we achieve this by identifying emission cutoffs at the lower hybrid frequency and electron plasma frequency. Further, we discuss the development of the process and tools for identifying and digitizing appropriate resonance and cutoff frequencies. Key Points: We develop a novel technique to determine electron densities in Jupiter's magnetosphere We describe how appropriate characteristic frequencies can be identified and digitized from plasma wave spectra We provide expected uncertainties for the density and some caveats for use